Rainwater Harvesting System for Generating Green Energy – Numerical Modelling - Zambre, Aleesya Ellanie (Universiti Teknologi PETRONAS, 2020)
Malaysia’s climate condition, with high humidity and large rainfall volumes, creates the potential function of utilizing small-scale hydropower through integration with rainwater harvesting systems. The study is conducted to produce an optimized rainwater harvesting system to generate electricity within Malaysian conditions and regulations. The project focuses on the conversion of rainwater into energy, therefore the components discussed are the gutter, downdrain system, and turbine only. The area of study is established as Kuala Lumpur and the appropriated rainfall values were identified. The eaves gutter was than designed, downdrain sized and Pelton turbine designed. In this, a parametric study was done to identify the critical parameters that affect the energy generation which is gutter slope, angle of deflection and tangential velocity. A Computational Fluid Dynamics simulation was done to study the relationship between the configuration, parameters, and energy generation.